2019
DOI: 10.1111/bph.14641
|View full text |Cite
|
Sign up to set email alerts
|

A proof‐of‐concept, Phase 2 clinical trial of the gastrointestinal safety of a hydrogen sulfide‐releasing anti‐inflammatory drug

Abstract: Background and Purpose ATB‐346 is a hydrogen sulfide (H2S)‐releasing anti‐inflammatory and analgesic drug. Animal studies demonstrated negligible gastrointestinal (GI) damage despite marked inhibition of COX activity and significant analgesic and anti‐inflammatory effects. In humans, ATB‐346 (250 mg once daily) was found to inhibit COX to the same extent as naproxen (550 mg twice daily). Experimental Approach Two hundred forty‐four healthy volunteers completed a 2‐week, double‐blind study, taking either ATB‐34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 43 publications
1
72
0
8
Order By: Relevance
“…In animal models, NSAIDs conjugated to H 2 S, i.e., naproxen and celecoxib, demonstrated a strong protective effect on gastrointestinal epithelium compared to the toxic effect of the parent drug [102]. For example, the H 2 S-releasing naproxen, called ATB-346, which releases H 2 S via a hydrolytic mechanism [102], was demonstrated to have a greater anti-inflammatory and chondro-protective effect on osteoarthritic joints in animal models, reducing leukocyte migration and reducing TNF-α and NF-κB expression, and less gastrointestinal toxicity [102,140,141]. Recently, a phase II clinical trial investigating 244 healthy subjects demonstrated a drastic reduction of gastric ulcer investigated with endoscopy when treated with ATB-346 (42.2% vs. 2.5% ulcer development with naproxen and ATB-346, respectively).…”
Section: H 2 S-donors As Potential Anti-arthritis Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, NSAIDs conjugated to H 2 S, i.e., naproxen and celecoxib, demonstrated a strong protective effect on gastrointestinal epithelium compared to the toxic effect of the parent drug [102]. For example, the H 2 S-releasing naproxen, called ATB-346, which releases H 2 S via a hydrolytic mechanism [102], was demonstrated to have a greater anti-inflammatory and chondro-protective effect on osteoarthritic joints in animal models, reducing leukocyte migration and reducing TNF-α and NF-κB expression, and less gastrointestinal toxicity [102,140,141]. Recently, a phase II clinical trial investigating 244 healthy subjects demonstrated a drastic reduction of gastric ulcer investigated with endoscopy when treated with ATB-346 (42.2% vs. 2.5% ulcer development with naproxen and ATB-346, respectively).…”
Section: H 2 S-donors As Potential Anti-arthritis Drugsmentioning
confidence: 99%
“…Recently, a phase II clinical trial investigating 244 healthy subjects demonstrated a drastic reduction of gastric ulcer investigated with endoscopy when treated with ATB-346 (42.2% vs. 2.5% ulcer development with naproxen and ATB-346, respectively). This effect was associated with an increased suppression of COX activity [141]. The efficacy of ATB-346 was recently evaluated in patients with OA, demonstrating that ATB-346 can reduce joint pain, possibly to a greater extent than other standard NSAIDs, such as naproxen or celecoxib [142].…”
Section: H 2 S-donors As Potential Anti-arthritis Drugsmentioning
confidence: 99%
“…However, novel CO-releasing prodrugs were developed recently and further studies will hopefully reveal their clinical potential [86]. It is worth to highlight, that H 2 S-releasing derivative of naproxen, ATB-346 with its reduced gastrotoxicity passed successfully the Phase 2 of clinical trial [24]. Taken together, there are still many missing aspects to be answered and extensively investigated in the context of CO and H 2 S-related physiology and pharmacology of GI digestive system.…”
Section: Conclusion Possible Implementation Into Therapy Of Gi Disomentioning
confidence: 99%
“…Moreover, H 2 S-releasing NaHS has been shown to accelerate ulcer healing and to attenuate non-steroidal anti-inflammatory drugs (NSAIDs)-induced gastrotoxicity [22,23]. Interestingly, H 2 S-releasing derivative of naproxen (ATB-346) which successfully completed phase 2 clinical trial, offers a promising safer alternative for conventional native form of this NSAID not only in improvement of pain relief but also in GI-safety manifested by the reduction of upper GI tract damage formation in subjects treated with equimolar effective doses of ATB-346 versus naproxen [24]. Similarly GYY4137, slow H 2 S-releasing compound has been shown to exert anti-inflammatory activity [25] and to decrease the area of ischemia/reperfusion-induced gastric damage in rats [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation